Assessment of nutrition and physical activity practices using self-report and observation in early care and education across multiple US states. Issue 9 (6th March 2017) - Smith, Teresa M; Blaser, Casey; Geno Rasmussen, Cristy; Shuell, Julie; Plumlee, Catherine; Yaroch, Amy L
Abstract: Objective: The National Early Care and Education Learning Collaboratives (ECELC) Project aims to promote healthy physical activity and nutrition environments, policies and practices in early care and education (ECE) programmes across multiple states. The present pilot study sought to assess changes to the physical activity and nutrition practices in a sub-sample of ECE programmes participating in the ECELC using the Environment and Policy Assessment and Observation (EPAO). Additionally, it sought to compare results with the Nutrition and Physical Activity Self-Assessment for Child Care (NAP SACC). Design: Quasi-experimental pre–post pilot study where paired-sample t tests examined changes to physical activity and nutrition practices from pre-assessment to post-assessment ( P <0·05). Pearson correlation coefficients examined change scores from EPAO compared with NAP SACC with statistical significance set at a two-sided α level of P <0·10 to account for sample size. Setting: The study occurred among ECE programmes. Subjects: Pre-school classrooms in nineteen ECE programmes across four US states were observed. Results: EPAO data demonstrated an increase in total score from pre-assessment to post-assessment (150 (sd 30) to 176 (sd 35)). NAP SACC change scores demonstrated little relationship with EPAO domain change scores, with exceptions in Nutrition Policy and Physical Activity Policy ( r =−0·4 and −0·6, respectively). Conclusions: The overall improvements reported through the EPAO suggest participation in the ECELC resulted in changes in critical nutrition- and physical activity-related practices. However, considerable differences in data reported using the NAP SACC compared with the EPAO suggest subjective data should be interpreted with caution and objective measurement should be used when feasible.